The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1259/dmfr/71465153
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of digital X-ray mini-panel examinations for patients having mental retardation and developmental disability

Abstract: Dental inspections of MR/DD patients are incomplete if radiographs are excluded. Whilst the mini-panel approach could be considered incomplete, it is better than no radiographs at all. 91% of images were excellent to satisfactory in diagnostic quality and a majority of patients' treatments were modified because of the radiographic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…They found one or more dental anomaly in 90% of patients and granuloma or cyst in 32% of patients, and reported that 60% of the patients' treatment plans were changed due to radiological findings. Only one patient was discharged from the study due to lack of cooperation [1]. In our study, all patients were uncooperative patients on whom we were unable to obtain PA or OPG.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…They found one or more dental anomaly in 90% of patients and granuloma or cyst in 32% of patients, and reported that 60% of the patients' treatment plans were changed due to radiological findings. Only one patient was discharged from the study due to lack of cooperation [1]. In our study, all patients were uncooperative patients on whom we were unable to obtain PA or OPG.…”
Section: Discussionmentioning
confidence: 90%
“…Patient cooperation is the main factor in ensuring and maintaining oral health. However, due to lack of cooperation, MHP/ UCPs are at high risk for poor oral and dental health [1]. Aşıcı et al showed that MHPs have more teeth erosions and decay/missing/filling teeth (DMFT) scores when compared with healthy patients [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As many factors contribute to the difficulty to obtain high-quality radiographs for PDD, a variety of techniques are needed to support patients in obtaining the necessary diagnostic images. One technique is to obtain fewer images, such as a mini-series of one periapical image in each sextant instead of a full mouth series [ 13 ]. Another technique is to obtain different types of images, such as the use of a panoramic image or oblique lateral radiographs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%